Hubungan antara Kekerasan Seksual dengan Fungsi Seksual Perempuan Di Kabupaten Jember (Association Between Sexual Violence with Female Sexual Function in Jember Regency) - Zuhratul Rofidah; Ni’mal Baroya; Dwi Martiana Wati (Pustaka Kesehatan, 2017)
Sexual violence affects women's sexual health. Sexual violence not only affects the reproductive organs physically, but also have an impact on psychological or mental condition of the victim. The goal of research to analyze the association between sexual violence with female sexual function in Jember regency through approach cross sectional research subjects are married women aged 25-40 years and living with a partner were 107 people with a sampling technique pusing method multistage random sampling. Data obtained are presented in tables and analyzed using chi-square test and logistic regression test with significance level of 95% (α = 0,05). The results showed that most women experience sexual coercion, so most women experience problems with sexual function. Women with age ≥ 30 years, low education level, did not work, low income, marital 0-9 years old, and has 2 children are more likely to experience sexual violence. Women with age ≥ 30 years, low education level, did not work, low income, marital 10-20 years old, and has 2 children are more likely to experience sexual dysfunction. The experience of sexual violence and the level of education is the most dominant factor for women to experience sexual dysfunction. It was necessary socialization and understanding of violence against women and female sexual function to improve the reproductive health of women. Keywords: Sexual Violence, Female Sexual Function, Sexual Dysfunction